Experimental characterization of various scale hydraulic signatures in a flooded branched street network. Issue 9 (21st October 2019) - Finaud-Guyot, P.; Garambois, P.-A.; Dellinger, G.; Lawniczak, F.; François, P.
ABSTRACT: Understanding urban flood flow repartition mechanisms within street network remains challenging. This paper presents an experimental dataset of water depth and velocity profiles in the Icube experimental rig. The spatial variability of discharge along a street is highlighted. Comparing the water depth gradient orientation and the flow repartition promotes for complex repartition mechanisms at small scales. Comparable unit-discharge values are observed in both large and narrow streets. Interestingly, the intensity of the discharge deviation at the crossroad scale is related with the asymmetry of the velocity profile entering a crossroad. Moreover, discharges at the crossroad and the subdistrict scales show that downscaling of the flow repartition relationship is difficult. At real scale, results show that inflow velocity profile asymmetry may persist on a distance of several street widths downstream of a crossroad. Such distances are insufficient to consider disconnected crossroads as done in the literature to establish discharge repartition relationships.